Vozmoznosti ispol'zovanija metoda stimuljacii biologicheskoj aktivnosti v podgotovke predstavitel'nic akademiceskoj grebli - Micheev, A. A. (Teorija i Praktika fiziceskoj Kul'tury, 2004)
6 elite female athletes specialized in boat racing took part in the researches carried out for the revealing of the efficacy of the procedure the stimulation of the biological potency with the purpose of the accelerated development of physical qualities. The research was carried out at the stage of training for the World championship. It was offered to carry out series of stimulating exercises to female athletes during three microcycles for the accelerated development of physical qualities. 8 trainings had been carried out. The duration of each excersise did not exceed 45 min., and cooperative time of vibrating action was 25 min. The results of researches have shown, that the accretion of parameters on all researched qualities of female athletes has authentically increased. The stimulation of the biological potency procedure allows to optimize the managerial process by physical preparedness, due to an opportunity of the accelerated development of physical qualities.